Comparison of virtual reality and real environment effects on perception of height in healthy individuals - Eda Karaman; Oğuz Yılmaz; Serkan Eti (PLoS ONE, 2025)
Purpose The aim of this study was to evaluate the effects of mechanically stimulated sacculus on our height perception. Methods Between 1.09.2022 and 30.06.2023, 52 volunteers, 27 women and 25 men, aged 20–50 years, were included in the study. Pure tone audiometry test, acoustic immittance, vestibular evoked myogenic potentials (VEMP) and mini mental tests (MMSE) were performed on these individuals. Afterwards, height estimations were made by looking from top to bottom and from bottom to top using mechanical stimulation in real environment and elevator simulation in virtual reality (VR) environment. Participants were informed in writing with an informed consent form and their signed consent was obtained. Results The averages of the height estimates made in the VR environment and in the real environment were compared with each other and no significant difference was observed (p > 0.05). When the height estimations made in the VR environment and in the real environment were compared with the current height value, a significant difference was observed only in the height estimation made by looking from the bottom up in the VR environment, and it was found to be higher than the current height (p < 0.05). When the height estimation values in the VR environment and in the real environment were compared with the place where height estimation was started, no significant difference was observed (p > 0.05). Conclusion In our study, the effect of the mechanical effect of the saccule on the height perception was investigated, and no significant difference was obtained in the height estimates made in the VR environment and in the real environment. Mechanical stimulation of the saccule is thought to have a limited role in height perception.